Microwave-Assisted Synthesis of Ceria-Zirconia Nanoparticles: Characterization and their Antimicrobial Studies - Ramasamy, Tamilselvi; Arunachalam, Thirumoorthi (Asian Journal of Chemistry, 2023)
Ceria-zirconia (CZAA) nanoparticles with varied molar ratio of 1:1, 0.8:0.2, 0.6:0.4, 0.4:0.6 and 0.2:0.8 labelled as CZAA-0, CZAA-1, CZAA-2, CZAA-3 and CZAA-4 were prepared using cerium nitrate, zirconium nitrate and ascorbic acid as promoter. The X-ray diffraction, scanning electron microscopy, ultraviolet-visible, Raman and Fourier transform infrared spectra were used to characterize the prepared nanoparticles. The prepared CZAA nanoparticles were tested for antibacterial activity against Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus and Enterococcus faecalis bacterial strains as well as Aspergillus niger, Penicillium and Candida albicans fungal strains using the well diffusion method. They were shown to be highly antimicrobial agents to all pathogenic strains tested.